An off-pump biatrial mini-maze procedure for treatment of long-standing persistent atrial fibrillation. (14th October 2021) - Yan, T; Zhu, S.J; Zhu, M; Guo, C.F
Abstract: Background: Surgical treatment has assumed a more prominent role in the therapy of atrial fibrillation (AF) with favorable efficiency and acceptable safety during the last decades. The traditional Cox-Maze procedure and Wolf Mini-Maze procedure focused on left atrial ablation. However, it is ubiquitous that patients with long-standing persistent atrial fibrillation (LSPAF) typically suffer from biatrial electrical and structural remodeling. The left atrial procedures are still not enough in patients with LSPAF. Purpose: Herein, we aimed to introduce a modified biatrial off-pump ablation procedure based on the Wolf Mini-Maze procedure and to detect the safety and efficacy of the surgery for patients with LSPAF. Methods: Between January 2016 and September 2020, 102 patients of LSPAF underwent our modified Mini-Maze procedure using bipolar radiofrequency ablation. Those patients firstly underwent a Mini-Maze procedure using Dallas lesion set, including video-assisted bilateral mini-thoracotomy, left atrial appendage excision, bilateral pulmonary vein isolation, ganglionic plexi evaluation and destruction, left atrial roof connecting lesion, and a linear lesion connecting this roofline to the root of the aorta at the junction of the left coronary and the non-coronary cusp. Secondly, a purse-string suture was performed on the right atrium, and then four ablation lesions were made to the superior vena cava, to the inferior vena cava, to the appendix of the right atrium, and to the tricuspid valve annulus from the purse-string suture point by the bipolar radiofrequency clamp. After the operation, the patients were followed up at an interval of 3, 6, 12 months, and every 1 year after that. Results: No mortality: No surgical re-exploration for bleeding. No permanent pacemaker implantation. 99 patients were free from LSPAF upon discharge. A follow-up at interval of 3, 6, 12, 24, 36, and 48 months showed a success rate free from LSPAF was 95.1% (97/102), 94.4% (85/90), 94.8% (73/77), 91.5% (54/59), 90.3% (28/31) and 100% (9/9), respectively Conclusions: The modified biatrial Mini-Maze suggested a safe and feasible procedure. Early follow-up demonstrated an acceptable success rate free from AF. It might have the potential to become another option for clinical treatment of LSPAF. Funding Acknowledgement: Type of funding sources: Public grant(s) – National budget only. Main funding source(s): General Program of the National Natural Science Foundation of China